Non-Prescription Drug Distribution in Italy: The Role of Large-Scale Retailers - Sabina Riboldazzi (European Scientific Journal, ESJ, 2017)
In recent years, a series of regulatory actions have reformed the Italian pharmaceutical supply chain, particularly that of non-prescription drugs. The present study analyzes the distribution phase of non-prescription drugs. Specifically, it focuses on the retail market of pharmaceuticals in Italy, highlighting the different sales formats and the role played by those large-scale retailers that have been able to develop new pharmaceutical offerings in their point of sales through dynamic management of retailing mix levers in a competitive perspective.